The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1007/bf00752387
|View full text |Cite
|
Sign up to set email alerts
|

The pre-intake drop-out at a community mental health center

Abstract: Characteristics of patients who failed to appear for their intake interviews at a community mental health center were contrasted with those who did follow through with their appointments. Findings suggest that characteristics associated with dropping out are likely to vary with patient groups. Show rates for adults who were seeking help for themselves were significantly related to parental status and the length of time from the day of scheduling an intake interview until that appointment. Patient-therapist gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 11 publications
1
13
0
3
Order By: Relevance
“…Interestingly, in the study by Foreman and Hanna, attendance was poorer among those who had been on the waiting list for more than 30 weeks or less than 4 weeks. Yet other studies have found no relationship of wait-time with appointment attendance (Beer 1991;Orme and Boswell 1991).…”
Section: Introductionmentioning
confidence: 95%
“…Interestingly, in the study by Foreman and Hanna, attendance was poorer among those who had been on the waiting list for more than 30 weeks or less than 4 weeks. Yet other studies have found no relationship of wait-time with appointment attendance (Beer 1991;Orme and Boswell 1991).…”
Section: Introductionmentioning
confidence: 95%
“…the relationship between waiting time and FTE was non-linear although this varies depending on the type of service. Orme and Boswell (1991) found attendance in a community mental health team was higher for appointments sent within 3 days or after 10 days. Hicks and Hickman (1994) found less than 2 weeks or greater than 12 weeks were associated with FTE in relationship counselling.…”
Section: Failure To Engage In Mental Health Servicesmentioning
confidence: 94%
“…Las características clínicas de los ausentes en las primeras citas corresponden a pacientes drogodependientes (3)(4)(5)(6) o aquellos que presentan quejas vagas y poco específicas (6,9) y suelen estar menos de acuerdo con la derivación que aquellos que, en contraste, acuden a petición propia y no suelen faltar (1,7). Por último, una mala accesibilidad geográfica del CSM y la lista de espera más larga se correlacionan con un mayor porcentaje de ausencias (1,3,4,6,11,15). Otros estudios han reflejado de forma anecdótica otros posibles factores influyentes como la hora de la cita (4), el profesional que va a atender al paciente (3), el hecho de que vaya a ser un residente (15) o el patrón estacional (4).…”
Section: Ausencias En Las Primeras Consultas De Un Centro De Salud Meunclassified
“…Estas investigaciones se han centrado principalmente en analizar las características personales, tanto clínicas como sociodemográficas, que puedan definir un perfil del paciente que no acude a estas primeras citas (1,(3)(4)(5)(6)(7)(8)(9)(10)(11) y en valorar las estrategias preventivas que se pueden llevar a cabo para paliar este problema (6,(12)(13)(14). Todos estos trabajos difieren en la metodología porque ésta se ha empleado en función de los aspectos particulares que analizan en cada estudio.…”
Section: Introductionunclassified